MEDICINAL PLANTS TRADITIONALLY USED IN MALI FOR DYSMENORRHEA - Sanogo, Rokia (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Dysmenorrhea is painful menstrual cramps, which negatively impacts the quality of life of a large percentage of the world’s female population in reproductive age. The paper reviews the plants used in the Malian traditional medicine for the treatment of dysmenorrhea. Some medicinal plants were effective for treatments of dysmenorrhea with minimal side effects. Conventional therapy for dysmenorrhea, which usually includes non-steroidal anti-inflammatory drugs (NSAIDs), provides symptomatic relief, but presents increasing adverse effects with long-term use. This article is in the framework of a study supported by International Foundation for Science (IFS) on three medicinal plants used in the treatment of dysmenorrhea in Mali: Maytenus senegalensis Stereospermum kunthianum and Trichilia emetica.